Complex fibroadenoma: bibliometric literature review and presentation of a clinical case - Cardoso, Ana Beatriz Aguiar; Schröder, Gabriele Cristina; Zimermann, Polyanna; Almendra, Thiago Santos Lima; Pinto, Antonione Santos Bezerra (Mastology, 2020)
Fibroadenomas (FAs) are benign fibro-epithelial tumours of the breast characterized by being biphasic and having stromal and epithelial components. It is estimated that FAs affect more than 20 percent of the general population aged 16–40 years old. Complex FAs are a sub-type of fibroadenoma presenting one or more pathological characteristics, such as epithelial calcifications, apocrine metaplasias, sclerosing adenoma and cysts larger than 3 mm. According to studies elsewhere, women with complex FAs are 3.1 times more likely to develop breast cancer. The objective of the present study was to map the scientific production of articles on complex FA in the international literature. The ISI Web of Knowledge (Web of Science), one of the main scientific databases in the world, was searched with the following terms: (“complex” and “fibroadenoma”) or (“fibroadenoma” and “complex”). Only articles published between 1981 and 2019 were considered for a bibliometric review, in which 160 articles from 126 different periodicals were identified after using refinement filters. Moreover, a clinical case was also discussed based on the patient’s medical record and interview.